2001
DOI: 10.1182/blood.v97.5.1360
|View full text |Cite
|
Sign up to set email alerts
|

Thymic emigrants isolated by a new method possess unique phenotypic and functional properties

Abstract: T cells that emigrate from the thymus have primarily been studied in vivo using fluorescent dye injection of the thymus. This study examined the properties of thymocytes that emigrate from cultured thymic lobes in organ culture. Under these conditions, thymic emigrants displayed the expected phenotype, that of mature thymocytes expressing high levels of T-cell receptor (TCR-␣␤) and either CD4 or CD8, and were observed to emigrate within 24 hours of positive selection. Emigration was inhibited by cytochalasin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 31 publications
6
36
0
Order By: Relevance
“…4, E and F) thymocytes were also increased in TCS1P 1 KO mice relative to controls. High expression of these markers is characteristic of fully mature thymocytes with potential for thymic emigration (30,31). In particular, single positive CD4ϩCD8Ϫ and CD4ϪCD8ϩ cells from TCS1P 1 KO mice expressed higher levels of CD62L than controls (Fig.…”
Section: Tcs1p 1 Ko Mice Have Decreased Numbers Of T-cell Lymphocytesmentioning
confidence: 99%
“…4, E and F) thymocytes were also increased in TCS1P 1 KO mice relative to controls. High expression of these markers is characteristic of fully mature thymocytes with potential for thymic emigration (30,31). In particular, single positive CD4ϩCD8Ϫ and CD4ϪCD8ϩ cells from TCS1P 1 KO mice expressed higher levels of CD62L than controls (Fig.…”
Section: Tcs1p 1 Ko Mice Have Decreased Numbers Of T-cell Lymphocytesmentioning
confidence: 99%
“…Phenotypically, RTE are distinct from most medullary thymocytes (8), yet as a group they also do not fully resemble peripheral naive T cells, as they collectively retain low levels of HSA and have not yet fully up-regulated Qa2 like their peripheral counterparts (8,16). Some RTE derived from neonatal mice may also express elevated levels of CTLA4 (17), which could suggest reduced functional capacity. In terms of function, an early study showed that the adult RTE proliferative and cytotoxic response to stimulation in vitro was similar to that of peripheral T cells (18).…”
mentioning
confidence: 99%
“…Another study, however, suggested that RTE, identified using a novel system involving the expression of GFP under the control of the RAG-2 promoter, were less able to up-regulate CD25 in response to stimulation and displayed an attenuated proliferative response (20). Similarly, RTE derived from fetal thymus organ culture were unable to elicit acute graftvs-host disease when transferred into allogeneic mice (17), although it is not clear whether the behavior of these in vitro RTE is equivalent to freshly isolated adult RTE. Collectively, these studies suggest that the thymic medullary sojourn sees positively selected thymocytes make the transition from being susceptible to deletion by TCR signaling, to acquiring the functional capacity to respond to TCR signals by undergoing activation, although this may not be fully complete until after they reach the periphery.…”
mentioning
confidence: 99%
“…Characterization of RTE has been controversial. Up-regulation of several markers on SP CD8 thymocytes undergoing positive selection and emigration, including CD5 (39), ␤ 7 integrin, CD44 and L-selectin (CD62L) has been reported (33,40), whereas others did not observe these changes (41). Our data further demonstrate the heterogeneity of the phenotypes of SP CD8 thymocyte subpopulations affected by positively selecting ligands, as well as difficulties in the precise characterization of the small subpopulation of RTE.…”
Section: Discussionmentioning
confidence: 68%